Postprandial hypoglycemia as a complication of bariatric and metabolic surgery: a comprehensive review of literature - Karimi, Mehdi; Kohandel Gargari, Omid (Frontiers in Surgery, 2024)
Postprandial hypoglycemia (PPH) is a challenging and significant complication that can occur following bariatric and metabolic surgery. Symptoms of PPH are typical of hypoglycemia, such as sweating, weakness, disorientation, palpitation, etc. The complex nature of PPH is essential to achieve accurate diagnosis and effective management. This review aims to give extensive coverage of the intricate nature of PPH common with bariatric and metabolic surgery, outlining its pathogenesis, risk factors, clinical presentation, diagnostic strategies, and treatment options. The study explores various clinical forms and pathogenic mechanisms behind PPH while discussing diagnostic tools like continuous glucose monitoring or mixed meal tolerance tests. Furthermore, it considers possible interventions, including dietary changes, pharmaceutical therapies, and surgeries, to relieve symptoms and improve patient's quality of life. It aims to comprehensively understand how healthcare professionals can effectively manage this disorder for patients undergoing bariatric and metabolic surgery.